EXTH-80. PBI-200: IN VIVO EFFICACY OF A NOVEL, HIGHLY CNS-PENETRANT NEXT GENERATION TRK INHIBITOR. (12th November 2021) - Pal, Kollol; Regina, Anthony; Elagoz, Aram; Albert, Vincent; Boudreault, Johnathan; Ouellet, Marc; Pilote, Louise; Bruneau-Latour, Nicolas; Wang, Hong; Tao, Limei; Bellavance, Edith; White, Peter; et al.
Abstract: TRK kinases (TRK) are clinically validated targets for cancers harboring NTRK gene fusions. However, approved TRK inhibitors (TRKi) give rise to mutations reducing long-term clinical efficacy, and display limited CNS penetration that may impact their ability to address primary brain tumors (PBT), including high-grade gliomas. Second generation compounds in development address some resistance mutations, but are not sufficiently CNS penetrant. PBI-200 is a novel, orally active TRK inhibitor designed to overcome resistance, with high CNS penetration. In vitro assays demonstrate picomolar- to nanomolar potency against both wild-type TRK and the major acquired resistance mutations. A BaF3 xenograft model encoding the LMNA-NTRK1 gene fusion and G595R solvent front mutation showed superior efficacy with PBI-200 relative to first-generation compounds larotrectinib and entrectinib, and equivalent efficacy to the second-generation compound selitrectinib, in terms of tumor growth inhibition. Importantly, drug concentrations in the brains of PBI-200 treated mice showed an approximately 4-fold brain/plasma ratio (BPR). In contrast, BPR of other TRKi were < 0.17, indicating that only PBI-200 achieved sustained drug levels in brain. PBI-200 demonstrated statistically superior CNS efficacy and survival in a KM12-Luc intracranial murine model, as compared to other TRKi (chi-squared 45.6, p < 0.0001). By day 41, 50% of mice in the PBI-200 group remained alive, whereas mice in the other treatment groups had died on or before day 32. Of note, no gross or histopathological CNS adverse effects were observed in a 14d CNS Field Observation Battery study. Finally, PBI-200 was the most selective TRKi in a 125 kinase panel (ThermoFisher) with only 1 off-target kinase inhibited > 60% at 1 micromolar. Together, these data suggest that PBI-200 has potential as a best-in-class, highly CNS-penetrant next generation TRKi. A Phase 1/2 clinical trial evaluating PBI-200 in NTRK fusion-positive patients, including patients with PBT, is ongoing (NCT04901806).